Biophysical studies of ligand selectivity for the hATG8 family of autophagy proteins - Butler, Kevin (2021)
Selective autophagy is a process by which potentially toxic material such as aggregated proteins, organelles and pathogens are specifically targeted and transported to autophagosomes and subsequent degradation by the lysosome. The process relies on selective autophagy receptor proteins (SARs) recognising cargo and then interacting with the six human autophagy related receptor proteins (hATG8) anchored to the membrane of the autophagosome. The interaction between SARs and hATG8 proteins requires a short amino acid sequence called an LC3 interacting region (LIR). LIRs consist of a core motif [W/F/Y]0-X1-X2-[L/V/I]3 with the aromatic residue often preceded by acidic residues. The LIR interacts with ATG8 proteins at a conserved binding site consisting of two hydrophobic pockets with aromatic and hydrophobic residues sitting in hydrophobic pockets one and two respectively. Neighbour of BRAC1 gene 1 (NBR1), unlike most SARs contains two LIRs and whilst both contain the core LIR motif they vary in the amino acids at the aromatic and hydrophobic position and the composition of amino acids preceding the aromatic residue. Using Biophysical methods the interaction of the two LIRs of NBR1 (Sequences containing 11-12 amino acids) with the hATG8 proteins were studied to gain a better understanding of the effect the different LIR sequence has on binding.